2021
DOI: 10.1080/17474086.2021.1935854
|View full text |Cite
|
Sign up to set email alerts
|

Oral ferroportin inhibitor vamifeport for improving iron homeostasis and erythropoiesis in β-thalassemia: current evidence and future clinical development

Abstract: Introduction: In β-thalassemia, imbalanced globin synthesis causes reduced red blood cell survival and ineffective erythropoiesis. Suppressed hepcidin levels increase ferroportin-mediated iron transport in enterocytes, causing increased iron absorption and potentially iron overload. Low hepcidin also stimulates ferroportin-mediated iron release from macrophages, increasing transferrin saturation (TSAT), potentially forming non-transferrin-bound iron, which can be toxic. Modulating the hepcidinferroportin axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…These findings suggest that Roxadustat plus oral iron contributes to mitigate the anemia symptoms in elderly patients with CKD and anemia, and facilitate the metabolism. The results may attributed to the fact that Roxadustat can reduce the hepcidin of the patient's body, thereby increasing the TRF level of the patient's body and helping the patient to stabilize the body's Fe level [ 14 , 15 ]. Rubeor et al revealed that the level of inflammatory factors in patients with CKD and anemia may have a certain relationship with the disease, and over half of the patients are accompanied by active inflammatory response [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that Roxadustat plus oral iron contributes to mitigate the anemia symptoms in elderly patients with CKD and anemia, and facilitate the metabolism. The results may attributed to the fact that Roxadustat can reduce the hepcidin of the patient's body, thereby increasing the TRF level of the patient's body and helping the patient to stabilize the body's Fe level [ 14 , 15 ]. Rubeor et al revealed that the level of inflammatory factors in patients with CKD and anemia may have a certain relationship with the disease, and over half of the patients are accompanied by active inflammatory response [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral iron is associated with adverse reactions such as gastrointestinal irritation. Roxadustat is a hypoxia-inducible factor prolyl hydroxylase inhibitor developed in recent years that can correct anemia via multiple pathways by inactivating prolyl hydroxylase Enzyme (PHD) under hypoxia, and regulating the main transcription factor of EPO gene; under normal circumstances, HIF- α and HIF- β that can be hydroxylated by PHD and degraded by the body bind to the nucleus and further bind to the hypoxia response element, thereby mediating gene transcription [ 14 ]. Hypoxia-inducible factor prolyl hydroxylase inhibitor induces functional HIF transcriptional response by stabilizing HIF and inhibiting PHD, and promotes the expression of erythropoietin receptor while promoting the production of endogenous EPO, thereby improving anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients reported improved symptoms, and adverse events consisted mainly of nonserious injection site reactions. Vamifeport is an orally administered small molecule drug which binds to ferroportin, blocks cellular iron export, and causes ferroportin internalization [ 44 ]. Vamifeport induced iron restriction and ameliorated β-thalassemia in preclinical models [ 45 ].…”
Section: Targeting Tmprss6 For Iron-restrictive Therapy In Hematologi...mentioning
confidence: 99%
“…The trial has been completed in November 2021, but the results are yet to be published. A phase IIb trial including adults with TDT is being planned with the primary objective to evaluate the efficacy of several increasing doses of vamifeport as measured by reduction in RBC transfusion burden [ 36 ]. Other molecules with hepcidin-like action may reduce iron absorption and redistribution and improve erythropoiesis.…”
Section: Thalassemiasmentioning
confidence: 99%